(untitled) (Discourse of Law and Administration, 2023)
In October 2022, in the opening speech at the annual conference of EU Ambassadors, EU High Representative Josep Borrell, in particular, noted that «many people in the world vote and elect their government, but their material conditions do not improve. And in the end, people want to live better. We need to explain the connection between political freedom and a better life. And we Europeans have this extraordinary chance. We live in a world, in this part of the world, where political freedom, economic prosperity, and social cohesion are the best, the best combination of all these ingredients. But the rest of the world is not like that. Our struggle is to try to explain that democracy, freedom, political freedom is something that cannot be exchanged for economic prosperity or social cohesion. Both of these topics should go hand in hand. Otherwise, our model will die. It will not be able to survive in this world.» Therefore, the world and Europe, in particular, and especially Ukraine, have entered the so-called bifurcation point. We do not know when and how they will come out of it. However, it is clear that the modern political and legal concept is changing, requiring either renewal or improvement. European civilization has already passed through such times, in particular, when Classical Greece and the Roman Empire were dying. Nevertheless, significant intellectual searches and reflections have always accompanied the processes of renewal or at least improvement of political and legal systems to the existing circumstances. It is not surprising that on the threshold of political and legal changes, the search for the content of the idea of justice occupied a central place in such intellectual explorations. The Middle Ages made a significant and invaluable contribution to the understanding of the idea of justice. Having certain flaws, this era became a certain bridge between Antiquity (in which the idea of justice received the highest philosophical and legal elaboration) and the New Age, in which justice as a philosophical idea and a legal concept was subjected to a significant transformation. Nevertheless, it is the historical approach to the study of the content of the idea of justice in the context of philosophy, law, and politics that can provide answers to questions about possible ways to solve modern social problems of the world.